Enterohepatic circulation of bile acids after cholecystectomy. Issue 7 (July 1978) - Roda, E; Aldini, R; Mazzella, G; Roda, A; Sama, C; Festi, D; Barbara, L
Abstract : Bile acid metabolism was investigated in 10 patients after cholecystectomy, 10 gallstone patients, and 10 control subjects. Diurnal variations of serum levels of cholic and chenodeoxycholic acid conjugates were not abolished by cholecystectomy. Cholic acid pool size was significantly reduced in cholecystectomised patients and the fractional turnover rate and the rate of intestinal degradation of bile acid showed a significant increase. In cholecystectomised patients fasting bile was supersaturated in cholesterol, though less than in gallstone patients, but, in both, feeding resulted in improvement of cholesterol solubility in bile. These data suggest that after cholecystectomy the small intestine alone acts as a pump in regulating the dynamics of the enterohepatic circulation of bile acids and that the improvement of cholesterol solubility in bile is due to a more rapid circulation of the bile acid pool in fasting cholecystectomised patients.